Method for improving interface reaction between ceramic shell and nickel-based superalloy

By forming an inert interface layer of yttrium oxide on the surface of the surface layer of the ceramic shell, the serious interface reaction between the ceramic shell and the nickel-based high-temperature alloy is solved, and the surface quality of the turbine blades and the economicality of the casting process are significantly improved.

CN119927143AActive Publication Date: 2025-05-06AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510113199.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-06
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

In the prior art, the interface between the ceramic shell and the nickel-based high-temperature alloy has serious reaction, resulting in sand-tight defects and affecting the surface quality and service life of the turbine blades.

Method used

The three vacuum heating and soaking process is used to place the ceramic shell into the yttrium oxide sol for treatment, forming an inert interface layer of yttrium oxide, which hinders the interface reaction between the highly reactive elements in the alloy and the ceramic shell surface layer material.

Benefits of technology

The interface reaction between the ceramic shell and the nickel-based high-temperature alloy is significantly improved, the sand sticking problem is reduced, the surface quality of the turbine blades is improved, and the difficulty of polishing and labor costs of precision casting parts are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119927143A_ABST
    Figure CN119927143A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving interface reaction between a ceramic shell and a nickel-based superalloy. The method comprises the following steps that surface layer slurry coating, surface layer sand spraying and coating and surface layer drying are sequentially conducted on a wax mold module; sequentially coating slurry on the back layer, spraying sand on the back layer and drying the back layer on the wax pattern module; the wax mold module is sequentially subjected to slurry coating of a slurry sealing layer and drying of the slurry sealing layer; the wax mold module is subjected to dewaxing treatment and roasting treatment, and a ceramic shell is obtained; and the ceramic shell is put into the yttrium oxide sol to be subjected to vacuum heating soaking treatment for three times, and then the yttrium oxide inert interface layer can be formed on the surface of the surface layer of the ceramic shell. According to the method, the yttrium oxide continuous inert reaction interface can be formed on the surface of the surface layer of the ceramic shell, so that the interface reaction between high-reaction-activity elements in the alloy and the surface layer material of the ceramic shell is hindered, the problem of burnt-on sand is avoided or relieved, and the surface quality of the turbine blade is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of precision casting of turbine blades, and in particular relates to a method for improving the interface reaction between a ceramic shell and a nickel-based high-temperature alloy. Background Art

[0002] As we all know, turbine blades are the components with the highest temperature requirements in the entire aircraft engine, and their service environment is very harsh. At present, the average melting point of turbine blades is around 1300℃, but they must work stably for a long time in an environment far higher than their own melting point. The temperature bearing capacity of turbine blades directly determines the temperature of the turbine front air inlet, thus affecting the power limit of the aircraft engine. This is why turbine blades are the most important core components of the entire aircraft engine.

[0003] At present, the main method for manufacturing turbine blades in the world is precision casting, which requires multiple processes such as wax model preparation, shell preparation, melting and pouring. The shell preparation process includes the following steps: first, a ceramic slurry composed of refractory powder, binder and organic additives is evenly coated on the surface of the wax model, and then refractory sand is used for sand pouring. After it is fully dried, the steps of coating slurry, sand pouring and drying are repeated, so that a layered ceramic shell composed of refractory slurry and refractory sand can be obtained.

[0004] The surface layer of the ceramic shell, that is, the first layer of ceramic slurry, is in direct contact with the molten liquid alloy. The temperature of the smelting process is generally above 1400°C. Under high temperature conditions, the chemical reaction between the materials is very intense, and the interface reaction between the elements of the surface layer material of the ceramic shell and the alloy liquid will aggravate defects such as sand adhesion, thereby destroying the surface quality of the casting. When the casting is subjected to grinding, the severe sand adhesion layer often requires deep grinding to be cleaned, but for castings with small dimensional tolerance bands such as thin walls, deeper grinding will cause the actual size of the turbine blade at the grinding part to be lower than the lower limit of the tolerance band, and the turbine blade can only be scrapped. Therefore, it is urgent to develop a method to improve the interface reaction between the ceramic shell and the nickel-based high-temperature alloy, so as to effectively reduce the probability of turbine blade scrapping due to grinding, and at the same time reduce the labor cost of manual grinding.

[0005] The invention patent with application publication number CN106311980A discloses a method for preparing a ceramic shell for high-temperature alloy directional / single crystal blade casting, which comprises the following steps: preparing a surface layer slurry, wherein the surface layer slurry contains alumina powder, silica sol, oxide powder (any one or more of yttrium oxide, chromium oxide, molybdenum oxide, tungsten oxide) and other substances; preparing a reinforcement layer slurry, wherein the reinforcement layer slurry contains alumina powder, silica sol and other substances; performing surface layer coating, reinforcement layer coating, sand pouring, drying and other operations on the wax mold; after dewaxing and roasting, a ceramic shell with anti-sand sticking is obtained. This technical solution prevents low-valent oxides from reacting with chromium in the alloy by pre-absorbing a certain amount of metal oxides through the surface layer coating, reduces the transfer of chromium in the alloy into the shell, and thus eliminates the tendency of chemical sand sticking. That is, this technical solution only reduces the sand sticking phenomenon of the ceramic shell through the surface layer material itself (limited material ratio, process parameters), and does not form an additional interface layer, so the sand sticking phenomenon still needs to be improved. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a method for improving the interface reaction between a ceramic shell and a nickel-based high-temperature alloy. The method comprises the following steps in order:

[0007] Step 1: According to the designed turbine blade structure, a turbine blade wax mold is pressed by a hot injection molding method, and a plurality of turbine blade wax molds are combined into a wax mold module;

[0008] Step 2: coating the wax mold module with slurry, pouring sand on the surface, and drying the surface to form the surface layer of the ceramic shell;

[0009] Step 3: After the surface coating is completed, the wax mold module is coated with slurry on the back layer, sprinkled with sand on the back layer, and dried on the back layer to form the back layer of the ceramic shell;

[0010] Step 4: After the back layer coating is completed, the wax mold module is coated with slurry and the sealing layer is dried to form a sealing layer of the ceramic shell;

[0011] Step 5: After the sealing slurry layer is applied, the wax mold module is placed in a dewaxing kettle for dewaxing treatment;

[0012] Step 6: After the dewaxing process is completed, the wax mold module is placed in a baking furnace for baking. After the baking process is completed, a ceramic shell can be obtained;

[0013] Step 7: Place the ceramic shell in the yttrium oxide sol and perform three vacuum heating and soaking treatments. After the three vacuum heating and soaking treatments are completed, an inert yttrium oxide interface layer can be formed on the surface of the ceramic shell, and the interface layer can improve the interface reaction between the ceramic shell and the nickel-based high-temperature alloy.

[0014] Preferably, in step 2, the slurry applied to the surface layer is a surface ceramic slurry, and the mass percentage of each substance in the surface ceramic slurry is 17-25wt% of zirconium acetate binder, 20-26wt% of zirconium oxide powder, 50-60wt% of white corundum powder, 0.2-0.8wt% of the first defoaming agent, and 0.2-0.8wt% of the first wetting agent, and the sum of the contents of each substance is 100wt%.

[0015] The ZrO2 content in the zirconium acetate binder is 20-30wt%; the mass percentage of each substance in the first defoamer is 45-55wt% of organic silane defoamer and 45-55wt% of n-octanol; the first wetting agent is a gemini siloxane wetting agent; the median particle size of the white corundum powder is 20-30μm, and the median particle size of the zirconium oxide powder is 15-25μm.

[0016] The preparation method of the surface ceramic slurry is as follows: first, the organosilane defoamer and n-octanol are evenly mixed at room temperature to obtain a first defoamer; then, the zirconium acetate binder, the first defoamer, and the first wetting agent are placed in a reactor and stirred at a temperature of 20-25°C for 10-30 minutes to allow the three substances to be completely fused; finally, zirconium oxide powder and white corundum powder are placed in a reactor and continued to be stirred at a temperature of 20-25°C for 1-5 hours to obtain a surface ceramic slurry; the outflow cup viscosity of the surface ceramic slurry is 10-30s.

[0017] The sand material used for the surface layer is corundum sand, and the particle size of the corundum sand is 100 meshes.

[0018] In any of the above schemes, preferably, in step 2, the wax model module is coated with slurry on the surface, sprinkled with sand on the surface, and dried on the surface, which includes the following steps in order:

[0019] Step (2-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the surface ceramic slurry in a direction perpendicular to the horizontal plane, and apply the slurry to the surface layer. The coating temperature is room temperature and the coating time is 20-40s;

[0020] Step (2-2): After the surface coating slurry is completed, the wax mold module is taken out from the surface ceramic slurry in a direction perpendicular to the horizontal plane, and the slurry is controlled by rotation. The slurry control temperature is room temperature and the slurry control time is 30-50s;

[0021] Step (2-3): After the rotation and slurry control are completed, the wax mold module is placed in the center of the sand spraying machine at an angle of 40-50 degrees to the horizontal plane, and the surface layer is sprayed with sand. The spraying temperature is room temperature and the spraying time is 30-40s. During the process of spraying the surface layer with sand, the wax mold module needs to be rotated at a constant speed to ensure that all parts of the wax mold module are evenly sprayed with sand, and then slightly shaken to control the floating sand;

[0022] Step (2-4): After the surface coating is completed, the wax mold module is placed in a drying room and the surface is dried at a temperature of 25-35°C, a humidity of 60-70%, and a drying time of 10-16 hours, thus completing the surface coating of the ceramic shell.

[0023] In any of the above schemes, it is preferred that in step three, the slurry coated on the back layer is a back layer ceramic slurry, and the mass percentage of each substance in the back layer ceramic slurry is 20-28wt% of silica sol binder, 16-22wt% of silicon powder, 52-60wt% of mullite powder, 0.2-0.8wt% of the second defoaming agent, and 0.2-0.8wt% of the second wetting agent, and the sum of the contents of each substance is 100wt%.

[0024] The SiO2 content in the silica sol binder is 20-30wt%; the mass percentage of each substance in the first defoamer is 45-55wt% of organic silane defoamer and 45-55wt% of n-octanol; the first wetting agent is a gemini siloxane wetting agent; the median particle size of the silicon powder is 15-25μm, and the median particle size of the mullite powder is 20-30μm.

[0025] The preparation method of the back layer ceramic slurry is as follows: first, the organosilane defoamer and n-octanol are evenly mixed at room temperature to obtain a first defoamer; then, the silica sol binder, the second defoamer, and the second wetting agent are placed in a reactor and stirred at a temperature of 20-25°C for 10-30 minutes to completely fuse the three substances; finally, silicon powder and mullite powder are placed in a reactor and continued to be stirred at a temperature of 20-25°C for 1-5 hours to obtain a back layer ceramic slurry; the outflow cup viscosity of the back layer ceramic slurry is 10-20s.

[0026] The sand material used for the back layer is corundum sand, and the particle size of the corundum sand is 16 meshes.

[0027] In any of the above schemes, preferably, in step three, the wax mold module is sequentially coated with slurry on the back layer, sprinkled with sand material on the back layer, and dried on the back layer, which includes the following steps in order:

[0028] Step (3-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the back layer ceramic slurry in a direction perpendicular to the horizontal plane, and coat the back layer with the slurry at room temperature for 20-40 seconds;

[0029] Step (3-2): After the back layer is coated with the slurry, the wax mold module is taken out from the back layer ceramic slurry in a direction perpendicular to the horizontal plane, and the slurry is controlled by rotation. The slurry control temperature is room temperature and the slurry control time is 30-50s;

[0030] Step (3-3): After the rotation and slurry control is completed, the wax mold module is placed in the center of the sand spraying machine at an angle of 40-50 degrees to the horizontal plane, and the back layer is sprayed with sand. The spraying temperature is room temperature and the spraying time is 30-40s. During the process of spraying the back layer with sand, the wax mold module needs to be rotated at a constant speed to ensure that all parts of the wax mold module are evenly sprayed with sand, and then slightly shaken to control the floating sand;

[0031] Step (3-4): After the back layer is sprinkled with sand material, the wax mold module is placed in a drying room and the back layer is dried at a drying temperature of 25-35°C, a drying humidity of 60-70%, and a drying time of 8-12 hours;

[0032] Step (3-5): Repeat the operations from step (3-1) to step (3-4) 1-6 times to complete the back layer coating of the ceramic shell.

[0033] In any of the above schemes, preferably, in step 4, the slurry applied to the sealing layer is a sealing layer ceramic slurry, which is the same as the back layer ceramic slurry; the wax mold module is sequentially coated with the sealing layer slurry and the sealing layer is dried, and the following steps are included in order:

[0034] Step (4-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the ceramic slurry of the sealing layer in a direction perpendicular to the horizontal plane, and apply the slurry to the sealing layer. The application temperature is room temperature and the application time is 20-40s. Step (4-2): After the application of the slurry to the sealing layer is completed, take the wax mold module out of the ceramic slurry of the sealing layer in a direction perpendicular to the horizontal plane, and rotate to control the slurry. The slurry control temperature is room temperature and the slurry control time is 30-50s.

[0035] Step (4-3): After the rotary slurry control is completed, the wax mold module is placed in a drying room and the sealing slurry layer is dried at a drying temperature of 25-35°C, a drying humidity of 60-70%, and a drying time of 8-12 hours, thus completing the coating of the sealing slurry layer of the ceramic shell.

[0036] In any of the above schemes, preferably, in step five, the dewaxing temperature of the wax mold assembly is 160-190° C. and the dewaxing time is 0.5-1 h.

[0037] In any of the above schemes, preferably, in step six, the wax mold assembly is calcined at a temperature of 700-1000° C. for 12-14 hours, and then cooled to room temperature in the furnace.

[0038] In any of the above schemes, preferably, in step seven, the ceramic shell is placed in the yttrium oxide sol for three vacuum heating soaking treatments, which includes the following steps in order:

[0039] Step (7-1): placing the ceramic shell in a vacuum impregnation kettle, and injecting yttrium oxide sol into the vacuum impregnation kettle at the same time, so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuating to a vacuum degree of 0.1-0.2MPa, and then heating to a temperature of 35-45°C, and soaking the ceramic shell at this vacuum degree and temperature for 25-35min; taking out the ceramic shell from the vacuum impregnation kettle, and standing at room temperature for 30-60min, thus completing the first vacuum heating soaking treatment;

[0040] Step (7-2): placing the ceramic shell into the vacuum impregnation kettle again, and at the same time adding an appropriate amount of yttrium oxide sol to the vacuum impregnation kettle so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuating to a vacuum degree of 0.1-0.2MPa, and then heating to a temperature of 50-60°C, and soaking the ceramic shell at this vacuum degree and temperature for 1-1.5h; taking out the ceramic shell from the vacuum impregnation kettle, and directly placing it in a drying furnace at 190-210°C for drying for 1-2h, and naturally cooling to room temperature, thereby completing the second vacuum heating and soaking treatment;

[0041] Step (7-3): Place the ceramic shell in the vacuum impregnation kettle again, and at the same time add an appropriate amount of yttrium oxide sol to the vacuum impregnation kettle so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuate to a vacuum degree of 0.1-0.2MPa, then heat to a temperature of 70-80°C, and soak the ceramic shell at this vacuum degree and temperature for 2-2.5h; take out the ceramic shell from the vacuum impregnation kettle, and directly place it in a drying furnace at 400-450°C for drying for 4-5h, and naturally cool to room temperature, thus completing the third vacuum heating and soaking treatment.

[0042] In any of the above schemes, preferably, after the three vacuum heating and immersion treatments are completed, an interface layer is formed on the surface of the surface layer of the ceramic shell, and the thickness of the interface layer is 1-10 μm.

[0043] In the present invention, the outflow cup viscosity of the surface ceramic slurry is limited to 10-30s. If the viscosity is too large, the fluidity of the slurry will be reduced, and the mold shell will have a heaping phenomenon, which will affect the quality of the surface layer. If the viscosity is too small, the coating amount will be small, the thickness of the surface slurry layer will be too low, and the sand will easily penetrate the slurry layer, resulting in damage to the surface layer during pouring, thereby causing inclusions and scrap. Similarly, the outflow cup viscosity of the back layer ceramic slurry is limited to 10-20s. If the viscosity is too large, the coating amount will increase, and the overall shell thickness and weight will increase significantly. If the viscosity is too small, the coating amount will decrease, and the overall shell thickness and weight will decrease significantly.

[0044] In the present invention, the impregnation liquid used in the vacuum heating immersion treatment is yttrium oxide sol, the main component of which is solid yttrium oxide, and has the characteristics of adhesiveness, thixotropy, easy dispersibility, water-soluble reversibility, suspension, adsorption and stability. During vacuum heating, the yttrium oxide sol will be micro-gelled on the surface of the ceramic shell to form an extremely thin yttrium oxide gel film, which will lose all the internal moisture after drying, and the solid yttrium oxide will directly adhere to the surface of the ceramic shell to form an interface layer similar to the yttrium oxide coating; during the melting and pouring process, the interface layer can effectively prevent the active elements in the highly reactive alloy from reacting with the surface material of the ceramic shell, thereby reducing the degree of sand adhesion and improving the surface quality of the turbine blades.

[0045] In the present invention, the ceramic shell is subjected to three vacuum heating soaking treatments, the heating temperature and soaking time are gradually increased, and the interface layer is gradually formed. After the first vacuum heating soaking treatment, the surface of the surface layer cannot form a complete interface layer; after the second vacuum heating soaking treatment, the surface of the surface layer gradually forms a complete interface layer; after the third vacuum heating soaking treatment, the surface of the surface layer forms a protective layer as a whole. The yttrium oxide sol is an aqueous solution, and the evaporation rate increases with the increase of the drying temperature, the adhesion of yttrium oxide on the ceramic shell increases, and the thickness of the formed protective layer also gradually increases.

[0046] In addition, the technical solution of the present invention is specifically used to improve the interface reaction between the ceramic shell and the nickel-based high-temperature alloy, and the interface reaction between the ceramic shell and the alloy liquid is completely different from the interface reaction between the ceramic core and the alloy liquid. Improving the interface reaction between the ceramic shell (i.e., the surface ceramic slurry of the ceramic shell) and the alloy liquid, that is, reducing the interface reaction of the outer surface of the turbine blade; improving the interface reaction between the ceramic core (i.e., the preparation material of the ceramic core) and the alloy liquid, that is, reducing the interface reaction of the inner cavity of the turbine blade. The preparation materials, preparation processes, and reaction mechanisms with the alloy liquid of the ceramic shell and the ceramic core are completely different. Vacuum immersion treatment is a common process in the preparation process of the ceramic core. In the technical field of improving the interface reaction between the ceramic shell and the alloy liquid, the present invention proposes the use of multiple vacuum heating immersion treatment technology, and each vacuum heating immersion treatment requires a different immersion temperature, immersion time, drying temperature, and drying time.

[0047] In the present invention, in the whole process of improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy, the ceramic shell finally needs to undergo three vacuum heating and immersion treatments. The process parameters of each vacuum heating and immersion are very important. At the same time, the material ratio and preparation parameters of the surface ceramic slurry and the back ceramic slurry are also very important. All parameters need to work synergistically to achieve the expected technical effect of the present invention.

[0048] In the present invention, the stirring equipment, manipulator, clamping equipment, slurry dipping equipment, sand spraying machine, drying furnace, vacuum impregnation kettle, dewaxing kettle, roasting furnace, etc. used are all traditional equipment, and there are no special requirements for the equipment structure and model. The hot injection molding method of the turbine blade wax mold is a traditional process, and there are no special requirements for the process flow, process parameters, pressing materials, pressing equipment, etc. After three vacuum heating and soaking treatments, the ceramic shell can be directly used in the subsequent casting process, and there are no special requirements for the casting process, casting parameters, etc.

[0049] The method of improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy of the present invention has the following beneficial effects:

[0050] (1) The present invention adopts three yttria sol vacuum heating immersion treatment steps to form an yttria continuous inert reaction interface on the surface of the ceramic shell, thereby hindering the interface reaction between the highly reactive elements in the alloy and the ceramic shell surface material, avoiding or reducing the sand sticking problem, and improving the surface quality of the turbine blades.

[0051] (2) The method of the present invention can significantly improve the serious interface reaction phenomenon that occurs on the surface layer of the conventional silica sol ceramic mold when high-reactivity alloys are poured, and the method effectively reduces the processing difficulty and labor cost of surface polishing of precision castings.

[0052] (3) In the present invention, during the three vacuum heating and immersion treatments, as the vacuum heating temperature and the vacuum immersion time gradually increase, the surface quality of the casting gradually improves, which indicates that the yttrium oxide sol forms a protective layer on the surface of the ceramic shell through vacuum heating immersion, thereby reducing the interface reaction between the highly reactive alloy and the surface of the ceramic shell, avoiding or reducing sand sticking defects. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 A process flow chart of a preferred embodiment of the method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to the present invention;

[0054] Figure 2 Surface photos of test panels prepared by the methods of the three embodiments (three vacuum heating immersion treatments);

[0055] Figure 3 This is a surface photograph of a test plate prepared by the method of Comparative Example 2 (one vacuum heating immersion treatment);

[0056] Figure 4 This is a surface photograph of a test plate prepared by the method of Comparative Example 3 (two vacuum heating immersion treatments);

[0057] Figure 5 The microscopic photographs are of test plates prepared by the methods of the three embodiments (three times of vacuum heating immersion treatment). DETAILED DESCRIPTION

[0058] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.

[0059] Embodiment 1:

[0060] like Figure 1 As shown, according to a preferred embodiment of the method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy of the present invention, the method comprises the following steps in chronological order:

[0061] Step 1: According to the designed turbine blade structure, a turbine blade wax mold is pressed by a hot injection molding method, and a plurality of turbine blade wax molds are combined into a wax mold module;

[0062] Step 2: coating the wax mold module with slurry, pouring sand on the surface, and drying the surface to form the surface layer of the ceramic shell;

[0063] Step 3: After the surface coating is completed, the wax mold module is coated with slurry on the back layer, sprinkled with sand on the back layer, and dried on the back layer to form the back layer of the ceramic shell;

[0064] Step 4: After the back layer coating is completed, the wax mold module is coated with slurry and the sealing layer is dried to form a sealing layer of the ceramic shell;

[0065] Step 5: After the sealing slurry layer is applied, the wax mold module is placed in a dewaxing kettle for dewaxing treatment;

[0066] Step 6: After the dewaxing process is completed, the wax mold module is placed in a baking furnace for baking. After the baking process is completed, a ceramic shell can be obtained;

[0067] Step 7: Place the ceramic shell in the yttrium oxide sol and perform three vacuum heating and soaking treatments. After the three vacuum heating and soaking treatments are completed, an inert yttrium oxide interface layer can be formed on the surface of the ceramic shell, and the interface layer can improve the interface reaction between the ceramic shell and the nickel-based high-temperature alloy.

[0068] In step 2, the slurry applied to the surface layer is a surface ceramic slurry, and the mass percentage of each substance in the surface ceramic slurry is 21wt% of zirconium acetate binder, 23wt% of zirconium oxide powder, 55wt% of white corundum powder, 0.5wt% of the first defoamer, and 0.5wt% of the first wetting agent. The content of ZrO2 in the zirconium acetate binder is 25wt%; the mass percentage of each substance in the first defoamer is 50wt% of organic silane defoamer and 50wt% of n-octanol; the first wetting agent is a geminisiloxane wetting agent; the median particle size of the white corundum powder is 25μm, and the median particle size of the zirconium oxide powder is 20μm.

[0069] The preparation method of the surface ceramic slurry is as follows: first, the organosilane defoamer and n-octanol are evenly mixed at room temperature to obtain a first defoamer; then, the zirconium acetate binder, the first defoamer, and the first wetting agent are placed in a reactor and stirred at a temperature of 22°C for 20 minutes to allow the three substances to be completely fused; finally, zirconium oxide powder and white corundum powder are placed in a reactor and continued to be stirred at a temperature of 22°C for 3 hours to obtain a surface ceramic slurry; the outflow cup viscosity of the surface ceramic slurry is 20s.

[0070] The sand material used for the surface layer is corundum sand, and the particle size of the corundum sand is 100 meshes.

[0071] In step 2, the wax model module is coated with slurry on the surface, sprinkled with sand on the surface, and dried on the surface, which includes the following steps in order:

[0072] Step (2-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the surface ceramic slurry in a direction perpendicular to the horizontal plane, and apply the slurry to the surface layer. The coating temperature is room temperature and the coating time is 30 seconds;

[0073] Step (2-2): After the surface coating slurry is completed, the wax mold module is taken out from the surface ceramic slurry in a direction perpendicular to the horizontal plane, and the slurry is controlled by rotation. The slurry control temperature is room temperature and the slurry control time is 40s;

[0074] Step (2-3): After the rotation and slurry control is completed, the wax mold module is placed in the center of the sand spraying machine at a 45-degree angle to the horizontal plane, and the surface layer is sprayed with sand. The spraying temperature is room temperature and the spraying time is 35 seconds. During the process of spraying the surface layer with sand, the wax mold module needs to be rotated at a constant speed to ensure that all parts of the wax mold module are evenly sprayed with sand, and then slightly shaken to control the floating sand;

[0075] Step (2-4): After the surface coating is completed, the wax mold module is placed in a drying room and the surface is dried at a drying temperature of 30°C, a drying humidity of 65%, and a drying time of 13 hours, thus completing the surface coating of the ceramic shell.

[0076] In step 3, the slurry coated on the back layer is a back layer ceramic slurry, and the mass percentage of each substance in the back layer ceramic slurry is 24wt% of silica sol binder, 19wt% of silicon powder, 56wt% of mullite powder, 0.5wt% of the second defoamer, and 0.5wt% of the second wetting agent. The SiO2 content in the silica sol binder is 25wt%; the mass percentage of each substance in the first defoamer is 50wt% of organic silane defoamer and 50wt% of n-octanol; the first wetting agent is a geminisiloxane wetting agent; the median particle size of the silicon powder is 20μm, and the median particle size of the mullite powder is 25μm.

[0077] The preparation method of the back layer ceramic slurry is as follows: first, the organosilane defoamer and n-octanol are evenly mixed at room temperature to obtain a first defoamer; then, the silica sol binder, the second defoamer, and the second wetting agent are put into a reactor and stirred at a stirring temperature of 22° C. for 20 minutes to allow the three substances to be completely fused; finally, silicon powder and mullite powder are put into the reactor and continued to be stirred at a stirring temperature of 22° C. for 3 hours to obtain a back layer ceramic slurry; the outflow cup viscosity of the back layer ceramic slurry is 15s.

[0078] The sand material used for the back layer is corundum sand, and the particle size of the corundum sand is 16 meshes.

[0079] In step three, the wax model module is coated with slurry on the back layer, sprinkled with sand on the back layer, and dried on the back layer, which includes the following steps in order:

[0080] Step (3-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the back layer ceramic slurry in a direction perpendicular to the horizontal plane, and coat the back layer with the slurry at room temperature for 30 seconds;

[0081] Step (3-2): After the back layer is coated with the slurry, the wax mold module is taken out from the back layer ceramic slurry in a direction perpendicular to the horizontal plane, and the slurry is controlled by rotation. The slurry control temperature is room temperature and the slurry control time is 40s;

[0082] Step (3-3): After the rotation and slurry control are completed, the wax mold module is placed in the center of the sand spraying machine at a direction of 45 degrees to the horizontal plane, and the back layer is sprayed with sand. The spraying temperature is room temperature and the spraying time is 35 seconds. During the process of spraying the back layer with sand, the wax mold module needs to be rotated at a constant speed to ensure that all parts of the wax mold module are evenly sprayed with sand, and then slightly shaken to control the floating sand;

[0083] Step (3-4): After the back layer is sprinkled with sand material, the wax mold module is placed in a drying room and the back layer is dried at a drying temperature of 30°C, a drying humidity of 65%, and a drying time of 10 hours;

[0084] Step (3-5): Repeat the operations from step (3-1) to step (3-4) 6 times to complete the back layer coating of the ceramic shell.

[0085] In step 4, the slurry applied to the sealing layer is a sealing layer ceramic slurry, which is the same as the back layer ceramic slurry; the wax mold module is sequentially coated with the sealing layer slurry and the sealing layer is dried, which includes the following steps in order:

[0086] Step (4-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the ceramic slurry of the sealing layer in a direction perpendicular to the horizontal plane, and apply the slurry to the sealing layer. The application temperature is room temperature and the application time is 30 seconds. Step (4-2): After the application of the slurry to the sealing layer is completed, take the wax mold module out of the ceramic slurry of the sealing layer in a direction perpendicular to the horizontal plane, and rotate and control the slurry. The slurry control temperature is room temperature and the slurry control time is 40 seconds.

[0087] Step (4-3): After the rotary slurry control is completed, the wax mold module is placed in a drying room and the sealing slurry layer is dried at a drying temperature of 30°C, a drying humidity of 65%, and a drying time of 10 hours, thus completing the coating of the sealing slurry layer of the ceramic shell.

[0088] In step five, the dewaxing temperature of the wax mold assembly is 175° C. and the dewaxing time is 0.8 h.

[0089] In step six, the wax mold assembly is calcined at 850°C for 13 hours, and then cooled to room temperature in the furnace.

[0090] In step seven, the ceramic shell is placed in yttrium oxide sol for three vacuum heating soaking treatments, which includes the following steps in order:

[0091] Step (7-1): placing the ceramic shell in a vacuum impregnation kettle, and injecting yttrium oxide sol into the vacuum impregnation kettle at the same time, so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuating to a vacuum degree of 0.15 MPa, and then heating to a temperature of 40°C, and soaking the ceramic shell at this vacuum degree and temperature for 30 minutes; taking out the ceramic shell from the vacuum impregnation kettle, and standing at room temperature for 45 minutes, thus completing the first vacuum heating soaking treatment;

[0092] Step (7-2): placing the ceramic shell into the vacuum impregnation kettle again, and at the same time adding an appropriate amount of yttrium oxide sol into the vacuum impregnation kettle so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuating to a vacuum degree of 0.15 MPa, and then heating to a temperature of 55°C, and soaking the ceramic shell at this vacuum degree and temperature for 1.2 hours; taking out the ceramic shell from the vacuum impregnation kettle, and directly placing it in a drying furnace at 200°C for drying for 1.5 hours, and naturally cooling to room temperature, thus completing the second vacuum heating and soaking treatment; Step (7-3): Place the ceramic shell in the vacuum impregnation kettle again, and add an appropriate amount of yttrium oxide sol to the vacuum impregnation kettle so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuate to a vacuum degree of 0.15MPa, then heat to a temperature of 75°C, and soak the ceramic shell at this vacuum degree and temperature for 2.2 hours; take out the ceramic shell from the vacuum impregnation kettle, and directly put it into a drying furnace at 425°C for drying for 4.5 hours, and naturally cool to room temperature, thus completing the third vacuum heating and soaking treatment. After three vacuum heating and soaking treatments, an interface layer is formed on the surface of the surface layer of the ceramic shell, and the thickness of the interface layer is 8μm.

[0093] The method of improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy in this embodiment has the following beneficial effects: (1) A three-step yttria sol vacuum heating soaking treatment process is used to form a continuous inert yttria reaction interface on the surface of the ceramic shell, thereby hindering the interface reaction between the highly reactive elements in the alloy and the ceramic shell surface material, reducing the sand sticking problem and improving the surface quality of the turbine blade. (2) The serious interface reaction phenomenon that occurs on the surface of the traditional silica sol ceramic shell when pouring highly reactive alloys can be significantly improved, and the method effectively reduces the difficulty and labor cost of surface polishing of precision castings.

[0094] Embodiment 2:

[0095] According to another preferred embodiment of the method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy of the present invention, its process flow, material ratio, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0096] In step 2, the slurry applied to the surface layer is a surface ceramic slurry, and the mass percentage of each substance in the surface ceramic slurry is 25wt% of zirconium acetate binder, 22wt% of zirconium oxide powder, 52wt% of white corundum powder, 0.2wt% of the first defoamer, and 0.8wt% of the first wetting agent. The content of ZrO2 in the zirconium acetate binder is 20wt%; the mass percentage of each substance in the first defoamer is 45wt% of organic silane defoamer and 55wt% of n-octanol; the first wetting agent is a geminisiloxane wetting agent; the median particle size of the white corundum powder is 20μm, and the median particle size of the zirconium oxide powder is 15μm.

[0097] The main preparation parameters of the surface ceramic slurry are: putting zirconium acetate binder, the first defoamer and the first wetting agent into the reactor and stirring them, the stirring temperature is 25°C, and the stirring time is 10 minutes; putting zirconium oxide powder and white corundum powder into the reactor and continuing to stir, the stirring temperature is 25°C, and the stirring time is 1 hour; the outflow cup viscosity of the surface ceramic slurry is 10 seconds.

[0098] The wax mold module is sequentially coated with slurry on the surface, sprinkled with sand on the surface, and dried on the surface. The main process parameters include: when coating the surface with slurry, the coating temperature is room temperature, and the coating time is 20s; when rotating the slurry, the slurry control temperature is room temperature, and the slurry control time is 30s; when sprinkled with sand on the surface, the wax mold module is at an angle of 40 degrees to the horizontal plane, the sprinkling temperature is room temperature, and the sprinkling time is 30s; when drying the surface layer, the drying temperature is 25°C, the drying humidity is 60%, and the drying time is 10h.

[0099] In step 3, the slurry coated on the back layer is a back layer ceramic slurry, and the mass percentage of each substance in the back layer ceramic slurry is 28wt% of silica sol binder, 17wt% of silicon powder, 54wt% of mullite powder, 0.2wt% of the second defoamer, and 0.8wt% of the second wetting agent. The SiO2 content in the silica sol binder is 20wt%; the mass percentage of each substance in the first defoamer is 45wt% of organic silane defoamer and 55wt% of n-octanol; the first wetting agent is a geminisiloxane wetting agent; the median particle size of the silicon powder is 15μm, and the median particle size of the mullite powder is 20μm.

[0100] The main preparation parameters of the back layer ceramic slurry are: putting the silica sol binder, the second defoaming agent and the second wetting agent into the reactor and stirring them, the stirring temperature is 25°C, and the stirring time is 10 minutes; putting the silicon powder and mullite powder into the reactor and continuing to stir, the stirring temperature is 25°C, and the stirring time is 1 hour; the outflow cup viscosity of the back layer ceramic slurry is 10 seconds.

[0101] The wax mold module is sequentially coated with slurry on the back layer, sprinkled with sand material on the back layer, and dried. The main process parameters include: when coating the back layer with slurry, the coating temperature is room temperature, and the coating time is 20s; when rotating the slurry, the slurry control temperature is room temperature, and the slurry control time is 30s; when sprinkled with sand material on the back layer, the wax mold module is at an angle of 40 degrees to the horizontal plane, the sprinkling temperature is room temperature, and the sprinkling time is 30s; when drying the back layer, the drying temperature is 25°C, the drying humidity is 60%, and the drying time is 8h; a total of 7 layers of back layer structure are coated.

[0102] In step 4, the slurry applied to the sealing layer is a ceramic slurry for the sealing layer, which is the same as the ceramic slurry for the back layer. The wax mold module is sequentially coated with the slurry for the sealing layer and dried. The main process parameters include: when the slurry is applied to the sealing layer, the coating temperature is room temperature and the coating time is 20s; when the slurry is rotated, the slurry control temperature is room temperature and the slurry control time is 30s; when the sealing layer is dried, the drying temperature is 25°C, the drying humidity is 60%, and the drying time is 8h.

[0103] In step 5, the dewaxing temperature of the wax mold assembly is 160° C. and the dewaxing time is 1 hour.

[0104] In step six, the wax mold assembly is calcined at 700°C for 14 hours and then cooled to room temperature in the furnace.

[0105] In step seven, the ceramic shell is placed in the yttrium oxide sol for three vacuum heating and soaking treatments, and the main process parameters include: in the first vacuum heating and soaking treatment, the vacuum is evacuated to a vacuum degree of 0.1MPa, heated to a temperature of 35°C, the ceramic shell is soaked for 25min at this vacuum degree and temperature, and the ceramic shell is left to stand at room temperature for 30min; in the second vacuum heating and soaking treatment, the vacuum is evacuated to a vacuum degree of 0.1MPa, heated to a temperature of 50°C, the ceramic shell is soaked for 1h at this vacuum degree and temperature, the drying temperature of the ceramic shell is 190°C, and the drying time is 2h; in the third vacuum heating and soaking treatment, the vacuum is evacuated to a vacuum degree of 0.1MPa, heated to a temperature of 70°C, the ceramic shell is soaked for 2h at this vacuum degree and temperature, the drying temperature of the ceramic shell is 400°C, and the drying time is 5h. After three vacuum heating and soaking treatments, an interface layer is formed on the surface of the surface layer of the ceramic shell, and the thickness of the interface layer is 10μm.

[0106] Embodiment three:

[0107] According to another preferred embodiment of the method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy of the present invention, its process flow, material ratio, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0108] In step 2, the slurry applied to the surface layer is a surface ceramic slurry, and the mass percentage of each substance in the surface ceramic slurry is 17wt% of zirconium acetate binder, 25wt% of zirconium oxide powder, 57wt% of white corundum powder, 0.8wt% of the first defoamer, and 0.2wt% of the first wetting agent. The content of ZrO2 in the zirconium acetate binder is 30wt%; the mass percentage of each substance in the first defoamer is 55wt% of organic silane defoamer and 45wt% of n-octanol; the first wetting agent is a geminisiloxane wetting agent; the median particle size of the white corundum powder is 30μm, and the median particle size of the zirconium oxide powder is 25μm.

[0109] The main preparation parameters of the surface ceramic slurry are: putting zirconium acetate binder, the first defoamer and the first wetting agent into the reactor and stirring them, the stirring temperature is 20°C, and the stirring time is 30 minutes; putting zirconium oxide powder and white corundum powder into the reactor and continuing to stir, the stirring temperature is 20°C, and the stirring time is 5 hours; the outflow cup viscosity of the surface ceramic slurry is 30 seconds.

[0110] The wax mold module is sequentially coated with slurry on the surface, sprinkled with sand on the surface, and dried on the surface. The main process parameters include: when coating the surface with slurry, the coating temperature is room temperature, and the coating time is 40s; when rotating the slurry, the slurry control temperature is room temperature, and the slurry control time is 50s; when sprinkled with sand on the surface, the wax mold module is at an angle of 50 degrees to the horizontal plane, the sprinkling temperature is room temperature, and the sprinkling time is 40s; when drying the surface layer, the drying temperature is 35°C, the drying humidity is 70%, and the drying time is 16h.

[0111] In step 3, the slurry coated on the back layer is a back layer ceramic slurry, and the mass percentage of each substance in the back layer ceramic slurry is 20wt% of silica sol binder, 21wt% of silicon powder, 58wt% of mullite powder, 0.8wt% of the second defoamer, and 0.2wt% of the second wetting agent. The SiO2 content in the silica sol binder is 30wt%; the mass percentage of each substance in the first defoamer is 55wt% of organic silane defoamer and 45wt% of n-octanol; the first wetting agent is a geminisiloxane wetting agent; the median particle size of the silicon powder is 25μm, and the median particle size of the mullite powder is 30μm.

[0112] The main preparation parameters of the back layer ceramic slurry are: putting the silica sol binder, the second defoaming agent and the second wetting agent into the reactor and stirring them, the stirring temperature is 20°C, and the stirring time is 30 minutes; putting the silicon powder and mullite powder into the reactor and continuing to stir, the stirring temperature is 20°C, and the stirring time is 5 hours; the outflow cup viscosity of the back layer ceramic slurry is 20 seconds.

[0113] The wax mold module is sequentially coated with slurry on the back layer, sprinkled with sand on the back layer, and dried. The main process parameters include: when coating the back layer with slurry, the coating temperature is room temperature, and the coating time is 40s; when rotating the slurry, the slurry control temperature is room temperature, and the slurry control time is 50s; when sprinkled with sand on the back layer, the wax mold module is at an angle of 50 degrees to the horizontal plane, the sprinkle temperature is room temperature, and the sprinkle time is 40s; when drying the back layer, the drying temperature is 35°C, the drying humidity is 70%, and the drying time is 12h; a total of 7 layers of back layer structure are coated.

[0114] In step 4, the slurry applied to the sealing layer is a ceramic slurry for the sealing layer, which is the same as the ceramic slurry for the back layer. The wax mold module is sequentially coated with the slurry for the sealing layer and dried. The main process parameters include: when the slurry is applied to the sealing layer, the coating temperature is room temperature and the coating time is 40s; when the slurry is rotated, the slurry control temperature is room temperature and the slurry control time is 50s; when the sealing layer is dried, the drying temperature is 35°C, the drying humidity is 70%, and the drying time is 12h.

[0115] In step 5, the dewaxing temperature of the wax mold assembly is 190° C. and the dewaxing time is 0.5 h.

[0116] In step six, the wax mold assembly is calcined at a temperature of 1000° C. for 12 hours, and then cooled to room temperature in the furnace.

[0117] In step seven, the ceramic shell is placed in the yttrium oxide sol for three vacuum heating and soaking treatments, and the main process parameters include: in the first vacuum heating and soaking treatment, the vacuum is evacuated to a vacuum degree of 0.2MPa, heated to a temperature of 45°C, the ceramic shell is soaked for 35min at this vacuum degree and temperature, and the ceramic shell is left to stand at room temperature for 60min; in the second vacuum heating and soaking treatment, the vacuum is evacuated to a vacuum degree of 0.2MPa, heated to a temperature of 60°C, the ceramic shell is soaked for 1.5h at this vacuum degree and temperature, the drying temperature of the ceramic shell is 210°C, and the drying time is 1h; in the third vacuum heating and soaking treatment, the vacuum is evacuated to a vacuum degree of 0.2MPa, heated to a temperature of 80°C, the ceramic shell is soaked for 2.5h at this vacuum degree and temperature, the drying temperature of the ceramic shell is 450°C, and the drying time is 4h. After three vacuum heating and soaking treatments, an interface layer is formed on the surface of the surface layer of the ceramic shell, and the thickness of the interface layer is 7μm.

[0118] Comparative Example 1:

[0119] After the ceramic shell is prepared, the comparative example does not undergo a vacuum heating soaking treatment process. The preparation process of the ceramic shell and the process parameters of each step are basically the same as those of the first embodiment.

[0120] Comparative Example 2:

[0121] After the ceramic shell is prepared, this comparative example undergoes a vacuum heating soaking treatment process. The ceramic shell preparation process and process parameters of each step are basically the same as those of Example 1, and the vacuum heating soaking treatment process and process parameters are basically the same as those of the first vacuum heating soaking treatment process of Example 1.

[0122] Comparative Example 3:

[0123] After the ceramic shell is prepared, the comparative example undergoes two vacuum heating and soaking treatment processes. The preparation process of the ceramic shell and the process parameters of each step are basically the same as those of Example 1, and the two vacuum heating and soaking treatment processes and process parameters are basically the same as the first vacuum heating and soaking treatment process and the second vacuum heating and soaking treatment process of Example 1.

[0124] The ceramic shells of the three embodiments and the three comparative examples were used for subsequent pouring processes respectively. The pouring process, pouring parameters, alloy liquid, etc. were the same. The thickness of the sand adhesion layer on the surface of the casting was tested respectively, as shown in Table 1.

[0125] Table 1 Test results of thickness of sand layer on casting surface

[0126] Test items Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Thickness of sand layer (μm) 3.51 3.07 3.93 52.5 31.96 20.44

[0127] The surface quality of the test panels prepared by the methods of the three embodiments (three vacuum heating immersion treatments) is as follows: Figure 2 As shown in the microscopic photographs Figure 5 As shown; the surface quality of the test plate prepared by the method of comparative example 2 (one vacuum heating immersion treatment) is as follows Figure 3 As shown; the surface quality of the test plate prepared by the method of comparative example 3 (two vacuum heating immersion treatments) is as follows Figure 4 shown.

[0128] From Table 1 and Figure 2-5 It can be seen that after the ceramic shells of the three embodiments have been subjected to three vacuum heating and immersion treatments, the thickness of the sand adhesion layer on the surface of the prepared castings is very small, even negligible, and the surface quality of the castings is very good, which indicates that the yttrium oxide sol is immersed in the surface of the ceramic shell through three vacuum heating treatments to form a good protective layer, thereby reducing the interface reaction between the highly reactive alloy and the surface of the ceramic shell and avoiding sand adhesion defects.

[0129] The yttrium oxide sol used in the above embodiments and comparative examples was purchased from Forsman Technology (Beijing) Co., Ltd., the zirconium acetate binder was purchased from Zhongshan Dixin Chemical Co., Ltd., the silica sol (model FSI silica sol) was purchased from Zhejiang Yuda Chemical Co., Ltd., the organosilane defoamer was purchased from Shandong Dinghong New Materials Co., Ltd., the gemini siloxane wetting agent (model LW-4100) was purchased from Dongguan Goode New Materials Co., Ltd., and other chemical reagents, powder materials, etc. were purchased from Aladdin Reagent Co., Ltd. and Sinopharm Chemical Reagent Co., Ltd.

[0130] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.

[0131] It is not difficult for those skilled in the art to understand that the method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy of the present invention includes any combination of the invention content and the specific implementation method of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for improving the interface reaction between a ceramic shell and a nickel-based high-temperature alloy, characterized in that: The method comprises the following steps in chronological order: Step 1: According to the designed turbine blade structure, a turbine blade wax mold is pressed by a hot injection molding method, and a plurality of turbine blade wax molds are combined into a wax mold module; Step 2: coating the wax mold module with slurry, pouring sand on the surface, and drying the surface to form the surface layer of the ceramic shell; Step 3: After the surface coating is completed, the wax mold module is coated with slurry on the back layer, sprinkled with sand on the back layer, and dried on the back layer to form the back layer of the ceramic shell; Step 4: After the back layer coating is completed, the wax mold module is coated with slurry and the sealing layer is dried to form a sealing layer of the ceramic shell; Step 5: After the sealing slurry layer is applied, the wax mold module is placed in a dewaxing kettle for dewaxing treatment; Step 6: After the dewaxing process is completed, the wax mold module is placed in a baking furnace for baking. After the baking process is completed, a ceramic shell can be obtained; Step 7: Place the ceramic shell in the yttrium oxide sol and perform three vacuum heating and soaking treatments. After the three vacuum heating and soaking treatments are completed, an inert yttrium oxide interface layer can be formed on the surface of the ceramic shell, and the interface layer can improve the interface reaction between the ceramic shell and the nickel-based high-temperature alloy.

2. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 1, characterized in that: In step 2, the slurry applied to the surface layer is a surface ceramic slurry, and the mass percentage of each substance in the surface ceramic slurry is 17-25wt% of zirconium acetate binder, 20-26wt% of zirconium oxide powder, 50-60wt% of white corundum powder, 0.2-0.8wt% of the first defoamer, and 0.2-0.8wt% of the first wetting agent, and the sum of the contents of each substance is 100wt%; The content of ZrO2 in the zirconium acetate binder is 20-30wt%; the mass percentage of each substance in the first defoamer is 45-55wt% of organic silane defoamer and 45-55wt% of n-octanol; the first wetting agent is a gemini siloxane wetting agent; the median particle size of the white corundum powder is 20-30μm, and the median particle size of the zirconium oxide powder is 15-25μm; The preparation method of the surface ceramic slurry is as follows: first, the organosilane defoamer and n-octanol are uniformly mixed at room temperature to obtain a first defoamer; then, the zirconium acetate binder, the first defoamer, and the first wetting agent are placed in a reaction kettle and stirred at a temperature of 20-25° C. for 10-30 minutes to completely fuse the three substances; finally, zirconium oxide powder and white corundum powder are placed in a reaction kettle and continue to stir at a temperature of 20-25° C. for 1-5 hours to obtain a surface ceramic slurry; the outflow cup viscosity of the surface ceramic slurry is 10-30 seconds; The sand material used for the surface layer is corundum sand, and the particle size of the corundum sand is 100 meshes.

3. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 2, characterized in that: In step 2, the wax model module is coated with slurry on the surface, sprinkled with sand on the surface, and dried on the surface, which includes the following steps in order: Step (2-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the surface ceramic slurry in a direction perpendicular to the horizontal plane, and apply the slurry to the surface layer. The coating temperature is room temperature and the coating time is 20-40s; Step (2-2): After the surface coating slurry is completed, the wax mold module is taken out from the surface ceramic slurry in a direction perpendicular to the horizontal plane, and the slurry is controlled by rotation. The slurry control temperature is room temperature and the slurry control time is 30-50s; Step (2-3): After the rotation and slurry control are completed, the wax mold module is placed in the center of the sand spraying machine at an angle of 40-50 degrees to the horizontal plane, and the surface layer is sprayed with sand. The spraying temperature is room temperature and the spraying time is 30-40s. During the process of spraying the surface layer with sand, the wax mold module needs to be rotated at a constant speed to ensure that all parts of the wax mold module are evenly sprayed with sand, and then slightly shaken to control the floating sand; Step (2-4): After the surface coating is completed, the wax mold module is placed in a drying room and the surface is dried at a temperature of 25-35°C, a humidity of 60-70%, and a drying time of 10-16 hours, thus completing the surface coating of the ceramic shell.

4. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 3, characterized in that: In step 3, the slurry coated on the back layer is a back layer ceramic slurry, and the mass percentage of each substance in the back layer ceramic slurry is 20-28wt% of silica sol binder, 16-22wt% of silicon powder, 52-60wt% of mullite powder, 0.2-0.8wt% of the second defoamer, and 0.2-0.8wt% of the second wetting agent, and the sum of the contents of each substance is 100wt%; The SiO2 content in the silica sol binder is 20-30wt%; the mass percentage of each substance in the first defoamer is 45-55wt% of organic silane defoamer and 45-55wt% of n-octanol; the first wetting agent is a gemini siloxane wetting agent; the median particle size of the silicon powder is 15-25μm, and the median particle size of the mullite powder is 20-30μm; The preparation method of the back layer ceramic slurry is as follows: first, the organosilane defoamer and n-octanol are uniformly mixed at room temperature to obtain a first defoamer; then, the silica sol binder, the second defoamer, and the second wetting agent are placed in a reaction kettle and stirred at a temperature of 20-25° C. for 10-30 minutes to completely fuse the three substances; finally, the silicon powder and the mullite powder are placed in the reaction kettle and continue to be stirred at a temperature of 20-25° C. for 1-5 hours to obtain the back layer ceramic slurry; the outflow cup viscosity of the back layer ceramic slurry is 10-20 seconds; The sand material used for the back layer is corundum sand, and the particle size of the corundum sand is 16 meshes.

5. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 4, characterized in that: In step three, the wax model module is coated with slurry on the back layer, sprinkled with sand on the back layer, and dried on the back layer, which includes the following steps in order: Step (3-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the back layer ceramic slurry in a direction perpendicular to the horizontal plane, and coat the back layer with the slurry at room temperature for 20-40 seconds; Step (3-2): After the back layer is coated with the slurry, the wax mold module is taken out from the back layer ceramic slurry in a direction perpendicular to the horizontal plane, and the slurry is controlled by rotation. The slurry control temperature is room temperature and the slurry control time is 30-50s; Step (3-3): After the rotation and slurry control is completed, the wax mold module is placed in the center of the sand spraying machine at an angle of 40-50 degrees to the horizontal plane, and the back layer is sprayed with sand. The spraying temperature is room temperature and the spraying time is 30-40s. During the process of spraying the back layer with sand, the wax mold module needs to be rotated at a constant speed to ensure that all parts of the wax mold module are evenly sprayed with sand, and then slightly shaken to control the floating sand; Step (3-4): After the back layer is sprinkled with sand material, the wax mold module is placed in a drying room and the back layer is dried at a drying temperature of 25-35°C, a drying humidity of 60-70%, and a drying time of 8-12 hours; Step (3-5): Repeat the operations from step (3-1) to step (3-4) 1-6 times to complete the back layer coating of the ceramic shell.

6. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 5, characterized in that: In step 4, the slurry applied to the sealing layer is a sealing layer ceramic slurry, which is the same as the back layer ceramic slurry; the wax mold module is sequentially coated with the sealing layer slurry and the sealing layer is dried, which includes the following steps in order: Step (4-1): Use a manipulator or related clamping equipment to clamp the wax mold module, immerse the wax mold module in the ceramic slurry of the sealing layer in a direction perpendicular to the horizontal plane, and apply the slurry to the sealing layer. The application temperature is room temperature and the application time is 20-40s. Step (4-2): After the application of the slurry to the sealing layer is completed, take the wax mold module out of the ceramic slurry of the sealing layer in a direction perpendicular to the horizontal plane, and rotate to control the slurry. The slurry control temperature is room temperature and the slurry control time is 30-50s. Step (4-3): After the rotary slurry control is completed, the wax mold module is placed in a drying room and the sealing slurry layer is dried at a drying temperature of 25-35°C, a drying humidity of 60-70%, and a drying time of 8-12 hours, thus completing the coating of the sealing slurry layer of the ceramic shell.

7. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 6, characterized in that: In step 5, the dewaxing temperature of the wax mold assembly is 160-190° C. and the dewaxing time is 0.5-1 h.

8. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 7, characterized in that: In step six, the wax mold assembly is calcined at a temperature of 700-1000° C. for 12-14 hours, and then cooled to room temperature in the furnace.

9. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 8, characterized in that: In step seven, the ceramic shell is placed in yttrium oxide sol for three vacuum heating soaking treatments, which includes the following steps in order: Step (7-1): placing the ceramic shell in a vacuum impregnation kettle, and injecting yttrium oxide sol into the vacuum impregnation kettle at the same time, so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuating to a vacuum degree of 0.1-0.2MPa, and then heating to a temperature of 35-45°C, and soaking the ceramic shell at this vacuum degree and temperature for 25-35min; taking out the ceramic shell from the vacuum impregnation kettle, and standing at room temperature for 30-60min, thus completing the first vacuum heating soaking treatment; Step (7-2): placing the ceramic shell into the vacuum impregnation kettle again, and at the same time adding an appropriate amount of yttrium oxide sol to the vacuum impregnation kettle so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuating to a vacuum degree of 0.1-0.2MPa, and then heating to a temperature of 50-60°C, and soaking the ceramic shell at this vacuum degree and temperature for 1-1.5h; taking out the ceramic shell from the vacuum impregnation kettle, and directly placing it in a drying furnace at 190-210°C for drying for 1-2h, and naturally cooling to room temperature, thereby completing the second vacuum heating and soaking treatment; Step (7-3): Place the ceramic shell in the vacuum impregnation kettle again, and at the same time add an appropriate amount of yttrium oxide sol to the vacuum impregnation kettle so that the ceramic shell is completely immersed in the yttrium oxide sol; first evacuate to a vacuum degree of 0.1-0.2MPa, then heat to a temperature of 70-80°C, and soak the ceramic shell at this vacuum degree and temperature for 2-2.5h; take out the ceramic shell from the vacuum impregnation kettle, and directly place it in a drying furnace at 400-450°C for drying for 4-5h, and naturally cool to room temperature, thus completing the third vacuum heating and soaking treatment.

10. The method for improving the interface reaction between the ceramic shell and the nickel-based high-temperature alloy according to claim 9, characterized in that: After the three vacuum heating and soaking treatments are completed, an interface layer is formed on the surface of the surface layer of the ceramic shell, and the thickness of the interface layer is 1-10 μm.

Citation Information

Patent Citations

  • Preparing method for ceramic molding shell for casting high-temperature alloy orientation / single crystal blade

    CN106311980A

  • 600-DEG C high-temperature titanium alloy fired mold casting type shell surface painting and preparation method thereof

    CN102151787A

  • Anti-interface reaction composite ceramic shell

    CN102950251A

  • Modification method for ceramic shell surface layer for titanium alloy casting

    CN106363131A

  • Silica sol precision casting shell modified silicon oxide powder and preparation and sintering forming process thereof

    CN111687373A